Analisis Kendala Penerapan Model Project-Based Learning (PjBL) Berbasis STEAM Berbantuan Artificial Intelligence dalam Pembelajaran IPA - Faradhillah; Fakhrah (Jurnal Kajian Pendidikan IPA, 2026)
This research has a high urgency due to the increasing trend of technology use so that higher education in Science, Technology, Engineering, Arts, and Mathematics (STEAM) is becoming increasingly important. The STEAM-based Project Based Learning (PjBL) model supported by Artificial Intelligence (AI) offers an innovative approach. In addition, the urgency of implementing this model lies in the need to prepare teachers to have digital competencies in facing real-world challenges. This study aims to identify obstacles faced by teachers in implementing the STEAM-based PjBL model assisted by AI in science learning in North Aceh. This study uses a qualitative approach with the Case Study Method, data in this study were collected through in-depth interviews with teachers and students, direct observation during the learning process, and analysis of curriculum documents and educational policies. The results of the study indicate that there are several obstacles, such as teachers' lack of understanding of the PjBL and STEAM models, limited technological facilities, and student resistance in adapting to project-based learning. The results show that teachers' low understanding of the PjBL and STEAM models, limited technological facilities, and student resistance indicate that the implementation of learning is not fully student-oriented (student-centered). The use of AI has the potential to support learning through data analysis, feedback, and individualized material adjustments. However, the teacher's role remains crucial in developing students' creativity, empathy, and critical thinking skills. This research is expected to provide recommendations for improving the effectiveness of the STEAM-based PjBL model in North Aceh.Keywords: AI, project-based learning, STEAM